2022
DOI: 10.1302/0301-620x.104b9.bjj-2021-1391.r3
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors for stress fracture following periacetabular osteotomy

Abstract: Aims The aims of this study were to characterize the incidence and risk factors associated with stress fractures following periacetabular osteotomy, and to determine their effect on osteotomy union. Methods We retrospectively reviewed all periacetabular osteotomies (PAOs) performed for developmental dysplasia of the hip (DDH) at one institution over a six-year period between 2012 and 2017. Perioperative factors were recorded, and included demographic and surgical data. Postoperatively, patients were followed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…61 It ranges from psychosocial burden from long rehabilitation to under-recognized debilitating stress fractures. 62 Unlike HA, which has an overall complication rate of 3% in a systematic review including 26,000 cases, PAO has been associated with a 7% complication rate, mostly due to wound problems and higher rates of nerve injuries. 63-65 In our cohort, 33% of hips had changes in the LFCN dermatome, but these did not influence the PROMs and were only reported when questioned or examined.…”
Section: Discussionmentioning
confidence: 96%
“…61 It ranges from psychosocial burden from long rehabilitation to under-recognized debilitating stress fractures. 62 Unlike HA, which has an overall complication rate of 3% in a systematic review including 26,000 cases, PAO has been associated with a 7% complication rate, mostly due to wound problems and higher rates of nerve injuries. 63-65 In our cohort, 33% of hips had changes in the LFCN dermatome, but these did not influence the PROMs and were only reported when questioned or examined.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are still very significant question marks over how and when periacetabular osteotomy should be performed, and what adjunctive treatments are needed. [21][22][23][24][25][26][27][28][29] A great deal more research is needed.…”
Section: Important Matters That Need Attentionmentioning
confidence: 99%
“… 2 If diagnosed in time, PAO is the surgical therapy of choice with the goal of preserving the native hip joint, relief of pain and maintenance of activity. 3 It was previously shown that both joint-specific function and quality of life improve after PAO. 4 …”
Section: Introductionmentioning
confidence: 97%
“…2 If diagnosed in time, PAO is the surgical therapy of choice with the goal of preserving the native hip joint, relief of pain and maintenance of activity. 3 It was previously shown that both joint-specific function and quality of life improve after PAO. 4 Age at the time of surgery, preoperative degree of osteoarthritis (OA), and preoperative joint-specific function are critical criteria to consider in the indication as they affect outcome.…”
Section: Introductionmentioning
confidence: 97%